If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x = 4 + 2x Solving 8x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8x + -2x = 4 + 2x + -2x Combine like terms: 8x + -2x = 6x 6x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 6x = 4 + 0 6x = 4 Divide each side by '6'. x = 0.6666666667 Simplifying x = 0.6666666667
| 14(-11s-19)= | | 1/2x+6=22 | | 5x-4x+x-5+3x= | | 5x^2+15x-54=0 | | 10+.10x=35x | | 7+5x+3x=7 | | 2*-7+4= | | -16(10-5z)+7z= | | 6w-8w=-10 | | -3x^2-5x=-2 | | 2(1-2z)-2(6z+3)=z-6 | | 4-7f=f+12 | | 28y^3-116y^2+16y= | | 45=5c+5 | | 61=-3x-5x-3 | | 2*(3+-10)+4= | | 9x+10=3x+11 | | -4x^2+8x=-6 | | 42=5c+5 | | 2h+1.5=2.5h | | -8(5r-17)= | | 1/4*n=4 | | 6+x=92 | | 12x^2+16x+4= | | 36x=(9*4)+(4*x)+(9*x) | | -5x^2-40x-78=0 | | 8ab-2x=-14 | | -23/3-11/8m=2m | | 2+9n=7y | | -4x+9+2x=5 | | 11x+7=-4 | | -18(7k+6)+5k= |